2016
DOI: 10.1007/s12035-016-9768-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Relationships Between Interleukin 15 mRNA and Brain-Derived Neurotrophic Factor II mRNA Levels With Formal Components of Temperament in Asthmatic Patients

Abstract: Asthma is a chronic inflammatory and heterogeneous disease developing mostly through allergic inflammation, which modifies the expression of various cytokines and neurotrophins. Previous studies suggest the involvement of interleukin (IL)-15 in the regulation of immune response in asthma. Brain-derived neurotrophic factor (BDNF) II plays an important role as a regulator of development and survival of neurons as well as maintenance of their physiological activity. Chronic stress associated with asthma and eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 54 publications
0
7
1
Order By: Relevance
“…High neuroticism means a tendency to depression and anxiety. Indeed, numerous other studies have confirmed that individuals with poor asthma control tend to be anxious and depressive [4,5,15]. Sastre et al have demonstrated that anxiety, depressiveness and a low forced expiratory volume in 1 s (FEV 1 ) value are independent risk factors for poor asthma control [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High neuroticism means a tendency to depression and anxiety. Indeed, numerous other studies have confirmed that individuals with poor asthma control tend to be anxious and depressive [4,5,15]. Sastre et al have demonstrated that anxiety, depressiveness and a low forced expiratory volume in 1 s (FEV 1 ) value are independent risk factors for poor asthma control [16].…”
Section: Discussionmentioning
confidence: 99%
“…It should be considered why poor control of asthma is related to neuroticism. Poor control of the disease means its severe course, the presence of dyspnea attacks, limitation of activity, and secondary anxiety and depression [4,5]. Thus, poorly controlled asthma can be viewed as a strong stresor that interferes with the functioning of the human being and leads to emotional disorders [11,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of infection in the course of bronchial asthma, numerous proinflammatory cytokines produced by several cell types are secreted, which correlates with the severity of depressiveness, which has been demonstrated in particular with respect to interleukin 5 [ 21 ]. Our own research has shown that the level of mRNA for interleukin 15 in patients with bronchial asthma correlates with the temperamental personality traits [ 22 ], and that there is a relationship between asthma patients’ personality and a polymorphism of the gene coding for the glucocorticosteroid receptor [ 9 ]. Depressiveness is often associated with anxiety, which, especially in the form of attacks, can induce bronchospasm in the course of asthma [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to anxiety, the predictors of severity of dyspnea included body mass index and value of forced expiratory volume in one second (FEV 1) [ 24 , 25 ]. In our own research, we have shown that the dimensions of temperament according to the concept developed in Poland by Strelau (in the regulatory temperament theory), and especially the low activity dimension, are associated with the severity of asthma and shortness of breath [ 24 , 25 ]. The personality structure, through the limbic system and the autonomic nervous system, influences the reactivity of the internal organs, including bronchospasm [ 26 ].…”
Section: Discussionmentioning
confidence: 99%